Citra Perempuan di Lembaran Buku Pendidikan Islam: Analisis Gender Pada Gambar Ilustrasinya - Titis Thoriquttyas (MUWAZAH : jurnal kajian gender, 2018)
This study aims to find out and analyze illustrations and mapping of material and illustration pictures of the Book Teaching of Fiqih, Al-Qur'an Hadith and Akidah Akhlak in class X MA 2013 curriculum in a gender perspective. The analysis uses two aspects: Macro aspects with an indicator of Marginalization, Subordination, Stereotype, Double Burden and Violence and Micro aspects with an indicator of Access, Participation, Control and Benefits. The results of the study show that, the illustrations in the three textbooks based on the macro and micro aspects provide space restrictions for women. The mapping of the tendency is still dominated by men, but on the other hand, the position of women and the rubrics that display both get a fairly high percentage